Arbeit und Melancholie - Vöing, Nerea

„Nicht alles lässt sich digital lösen“ – Jetzt schlägt die Stunde moderner Konzepte, meint Hochschuldidaktikerin Nerea Vöing - Vöing, Nerea (DUZ Magazin)

Besondere Formate der hochschuldidaktischen Weiterbildung. Stand der Praxis inklusive Good Practice-Beispiele - Vöing, Nerea; Franke, Kathrin; Sekyra, Anita (Handbuch Hochschuldidaktik)

»Ich bin froh darüber, dass das so passiert ist« - Kordts-Freudinger, Robert; Bücker, Diana; Schulte, Rebecca; Vöing, Nerea (Hochschule auf Abstand)

„Evidenz“, was meinen Sie damit? – Eine Interviewstudie zum Verständnis von Hochschullehrenden vom Evidenzbegriff - Vöing, Nerea; Leschke, Jonas; Daumiller, Martin (ZFHE)

Grenzen der Musik? Deutschsprachige Narrative zu Musik und Geräusch in den 1950er-Jahren - Tumat, Antje (Musikwissenschaft der Vielfalt. Festschrift Rebecca Grotjahn zum 60. Geburtstag)
Keywords: Neue Musik

Neue Wege in die Biologie: Verstehen mit Modellen - Originale – Theorien – Modellierung - Meister, Johannes; Trier, Ulrike; Upmeier zu Belzen, Annette

Attachment representation and emotion recognition ability in children with ADHD and their parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Krischer, M.; Susewind, M. (International Journal of Environmental Research and Public Health)

Zur inklusiven Betreuung von Kindern mit (drohender) Behinderung in Kindertageseinrichtungen in Bayern und im Rheinland. Ein Studienvergleich - Kißgen, R.; Wirts, C.; Limburg, D.; Wertfein, M.; Franke, Sebastian; Wölfl, J.; Austermühle, J. (Frühförderung interdisziplinär)

Attachment Representation and Emotion Recognition Ability in Children with ADHD and Their Parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Susewind, M.; Krischer, M. (International Journal of Environmental Research and Public Health)

Die Anfänge der Internationalen Ferienkurse für Neue Musik aus Gender-Perspektive - Tumat, Antje (Gender und Neue Musik)

Infant-Father Attachment in Infants Born Preterm. A Brief Report - Kissgen, R.; Franke, Sebastian; Jorjadze, N.; Roth, B.; Kribs, A. (International Journal of Developmental Science)

Exploring the paths towards service growth in manufacturing companies - Harrmann, L.; Böhm, Eva; Eggert, A. (2021 AMA Winter Academic Conference)

Ein kaiserlicher Wüterich und zwei antagonistische Simons. Der „Nero furens“ als Beispiel aus dem Paderborner Jesuitendramenkorpus - Elit, Stefan (NlatJb 23)

The Impact of Virtual Reality, Augmented Reality, and Interactive Whiteboards on the Attention Management in Secondary School STEM Teaching - Erofeeva, Maria; Klowait, Nils Oliver (2021 7th International Conference of the Immersive Learning Research Network (iLRN))

The Impact of Virtual Reality, Augmented Reality, and Interactive Whiteboards on the Attention Management in Secondary School STEM Teaching - Erofeeva, Maria; Klowait, Nils (2021 7th International Conference of the Immersive Learning Research Network (iLRN))

Hochschule auf Abstand
Trotz massiver Förderungen für die Digitalisierung ist die Präsenzlehre noch immer der Standard an deutschen Hochschulen. Aufgrund des Physical Distancing im Zuge der Corona-Pandemie musste sie jedoch kurzfristig fast vollständig digitalisiert werden. Die Beiträge des Bandes bieten einen multiperspektivischen Zugang zu den damit verbundenen Herausforderungen und beleuchten, wie die verschiedenen Akteur*innen die Umstellung auf digitale Lehr- und Lernformate umgesetzt und erlebt haben. Durch die Zusammenführung der verschiedenen Sichtweisen können die Bedarfe und Wünsche der einzelnen Akteursgruppen zusammengebracht und bei der nachhaltigen Weiterentwicklung der Hochschullehre besser berücksichtigt werden.

Engaging a product-focused sales force in solution selling: interplay of individual- and organizational-level conditions - Salonen, Anna; Terho, Harri; Böhm, Eva; Virtanen, Ari; Rajala, Risto (Journal of the Academy of Marketing Science)
Abstract This study explains how manufacturers tackle the critical managerial challenge of transforming a product-focused sales force to undertake solution selling. Through an application of configurational theory, the authors explain how individual and organizational conditions combine to determine salespeople’s engagement in solution selling. Multilevel, multisource data from the sales organization of a global supplier of building solutions represent input from salespeople ( N = 184), solution champions ( N = 23), and sales managers ( N = 26). A fuzzy set qualitative comparative analysis reveals no single, optimal way to overcome transformation challenges. Rather, consistent with prior research, solution selling requires certain types of salespeople, because value-based selling is a necessary condition for successful engagement. Beyond this foundational condition, a heterogeneous sales force can be engaged, as long as the organization provides appropriate support that is tailored to individual salespersons’ needs. The findings affirm that this viable support can come from either sales managers or solution champions.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Online reviews generated through product testing: can more favorable reviews be enticed with free products? - Garnefeld, Ina; Krah, Tabea; Böhm, Eva; Gremler, Dwayne D. (Journal of the Academy of Marketing Science)
Abstract Online reviews have profound impacts on firm success in terms of sales volume and how much customers are willing to pay, yet firms remain highly dependent on customers’ voluntary contributions. A popular way to increase the number of online reviews is to use product testing programs, which offer participants free products in exchange for writing reviews. Firms that employ this practice generally hope to increase review quality and secure higher product rating scores. However, a qualitative study, experimental study, and multilevel analysis of a field study dataset of more than 200,000 online reviews by product testers combine to reveal that product testing programs do not necessarily generate higher quality reviews, nor better product ratings. Only in certain circumstances (e.g., higher priced products) does offering a product testing program generate these benefits for the firm. Therefore, companies should consider carefully if and when they want to offer product testing programs.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Outcome-based contracting from the customers' perspective: A means-end chain analytical exploration - Schaefers, Tobias; Ruffer, Stefan; Böhm, Eva (Industrial Marketing Management)
Keywords: Marketing